Representation of Socio-Economic Activities and Conflict in Traditional Oral Narratives of the Tharaka People in Kenya. - Kwenga-Muriungi, Colomba Kaburi (Advances in Social Sciences Research Journal, 2019)
This study looks at oral narratives collected from the Tharaka people who live on the eastern region of Kenya, in Tharaka Nithi County. The Tharaka people were from time immemorial pastoralists and peasant farmers, who often had conflicts with the neighboring communities and amongst themselves. This background was often reflected in their oral literature and this is what this research pays attention to. My thesis in this paper will be that oral literature in any community acts as a memory reservoir for the community. The research explores how oral narratives help to represent the society’s economic activities and in re-narrating and configuring the types of conflict that the community experienced in the past. The narratives were collected through identifying expert oral narrators and recording oral narratives from them. Narratives were purposively sampled to get a population of narratives enough for the analysis done in this paper. The study concludes that preservation of such genres helps in not just representation of the economic activities of a community but they also help in preserving the community’s past experiences, specifically, the history of conflict and conflict resolution in pre-literate communities in Africa.